310 "The "Bright Falx" Sign - Midline Embolic Penetration is Associated With Faster Resolution of CSDH Following MMA Embolization. (April 2023) - Samarage, Hasitha Milan; Kim, Wi Jin; Colby, Geoffrey P.
Abstract : INTRODUCTION: CSDHs are common in the elderly and patients taking antiplatelet/anticoagulation medications. MMA embolization has become an adjunctive treatment to observation and surgery. Despite many embolization techniques, best practices for optimal CSDH resolution remain unknown. METHODS: Retrospective chart review was done on all patients who underwent MMA embolization for CSDHs between January 2017 and June 2021. Patient demographics, clinical presentation, anticoagulant use, and radiographic features were collected. Pre- and post-embolization CT scans were analyzed for volumetric changes and assessed for midline penetration of embolic material in the falx. RESULTS: MMA embolization was performed in 37 patients and 53 hemispheres. Older patients took longer to obtain complete resolution of CSDHs (r = 0.47, p = 0.03). Patients with larger pre-embolization (r = 0.57, p = 0.007) and post-embolization (r = 0.56, p = 0.008) CSDH volumes took longer to completely resolve. Patients who had nBCA embolization with midline penetration, as evidenced by the "bright falx" sign, had faster improvement rates than those who did not (5.64 cm 3 /d vs. 1.2 cm 3 /d, p = 0.02). CONCLUSIONS: Distal penetration of embolic material, particularly nBCA, into the falx may lead to more rapid improvement of CSDH.